EARNINGS OPACITY ON SHARE PRICE ANNUALIZED VOLATILITY AMONG QUOTED NON-FINANCIAL COMPANIES AT NAIROBI SECURITIES EXCHANGE - Stephen Ndirangu Maina; Tabitha Nasieku; Julius Miroga Bichanga (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The study examined the effect of earnings opacity on share price annualized volatility among non-financial companies quoted at Nairobi Securities Exchange. Earnings opacity is a measure that reflects how little information there is in a firm’s earnings number about its true, but unobservable, economic performance. The study was guided by pragmatic research philosophy and adopted a quantitative research design to evaluate earnings opacity and share price annualized volatility among quoted non-financial firms at Nairobi securities exchange. A census study of 39 non -financial companies quoted at the NSE was employed, of which 33 met data requirements. The study used secondary data from audited annual financial reports of the quoted firms for twenty years, from January 2003 through December 2022. The data collected was analysed using descriptive and inferential statistics. The hypothesis that there is no significant effect of earnings opacity on share price annualized volatility among quoted non-financial companies at Nairobi Securities was tested at a 95% confidence interval using t-statistic and p-value. The study used panel data Ordinary Least Square method technique for research analysis. Panel regression analysis using random effects model was conducted after necessary normality, model specification, homoscedasticity, linearity and autocorrelation diagnostic tests. Weighted Least Squares (WLS) is the preferred model for correcting heteroscedasticity and improving model fit. Findings show that earnings opacity had a significant effect (p = 0.00014, R² ≈ 0.022) on share price annualized volatility, among quoted non-financial firms at the Nairobi Securities Exchange. The findings provide critical insights for investors, regulators, and policymakers seeking to enhance market transparency and reduce informational risk in emerging capital markets.